Ende der Milchquote – Perspektiven und Ziele österreichischer Molkereien und MilchproduzentInnen - Erwin Schmid; Manuela Larcher; Martin Schönhart; Caroline Stiglbauer (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2011)
– The phasing-out of the EU milk quota regime in 2015 challenges the Austrian milk sector and calls for its re-organization. Private raw milk management systems and contracts between milk producers and milk processors and traders will replace the national milk quota regime. The aim of the study is to provide information to political and private agents on future contracts and the re-organization of the dairy sector. Consequently, we use qualitative interviews and quantitative surveys to reveal the perspectives, preferences, and aims of dairy CEOs and milk producers in Austria. The surveys follow a case study approach. We have selected eight dairies based on distinct criteria to conduct face to face interviews as well as a standard questionnaire procedure. Furthermore, a stratified sample of 1,500 corresponding milk producers has been drawn to perform a standard questionnaire procedure as well. A main part of the surveys focuses on the design of contracts between dairies and milk producers. Consequently, the study reveals common and distinct interests between the dairies' CEOs and milk producers. Comparisons to two Austrian and one German study provide an overview on the development of milk producer perspectives over time and the specificities of the Austrian milk sector. The results reveal a rather heterogeneous milk sector with respect to the perspectives, preferences, and aims among as well as between the groups of milk producers and dairies' CEOs. Although some accordance is given with some issues such as contract duration and termination clauses, other issues such as the regulation of raw milk deliveries indicate diverging interests between dairies and milk producers
Keywords: Q; Q0; Q00; 330; milk quota; EU; dairy farming; survey